2020
DOI: 10.3758/s13414-020-01992-6
|View full text |Cite
|
Sign up to set email alerts
|

Visual information is required to reduce the global effect

Abstract: When a distractor appears in close proximity to a saccade target, the saccadic end point is biased towards the distractor. This socalled global effect reduces with the latency of the saccade if the saccade is visually guided. We recently reported that the global effect does not reduce with the latency of a double-step memory-guided saccade. The aim of this study was to investigate why the global effect in memory-guided saccades does not show the typically observed reduction with saccadic latency. One possibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…Indeed, the saccade endpoint distributions obtained in the different spatial predictability conditions for a go-signal delay of 100 ms approached each other, which suggests that already a short prolongation of visual processing time can compensate for the adverse effect of spatial uncertainty on saccade accuracy. Such a dependency of top-down oculomotor control on exposure to task-relevant visual input is in line with recent evidence from a study on memory guided saccades (Arkesteijn, Donk, Smeets, & Belopolsky, 2020), which showed that sufficient target and distractor presentation time reduces saccade averaging.…”
Section: The Influence Of Visual Processing Time On Saccade Accuracy supporting
confidence: 86%
“…Indeed, the saccade endpoint distributions obtained in the different spatial predictability conditions for a go-signal delay of 100 ms approached each other, which suggests that already a short prolongation of visual processing time can compensate for the adverse effect of spatial uncertainty on saccade accuracy. Such a dependency of top-down oculomotor control on exposure to task-relevant visual input is in line with recent evidence from a study on memory guided saccades (Arkesteijn, Donk, Smeets, & Belopolsky, 2020), which showed that sufficient target and distractor presentation time reduces saccade averaging.…”
Section: The Influence Of Visual Processing Time On Saccade Accuracy supporting
confidence: 86%
“…This time course might rely on the same oculomotor inhibition responsible for the dynamic changes observed in saccade curvature (van der Stigchel 2010 ). Second, the global effect can be reduced by the presence of visual information (Arkesteijn et al 2020 , 2018 ). Third, it occurs independent of whether a saccade is preprogrammed or not (Arkesteijn et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the global effect can be reduced by the presence of visual information (Arkesteijn et al 2020 , 2018 ). Third, it occurs independent of whether a saccade is preprogrammed or not (Arkesteijn et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saccade trajectories have been found to curve toward distractors before finally landing somewhere between a target and distractor (McSorley et al, 2006;Mulckhuyse, Van der Stigchel, & Theeuwes, 2010). The actual trajectory and landing position depends on a number of factors such as separation, saliency, discriminability, the continuous availability of visual information, and saccade latency (Arkesteijn, Donk, Smeets, & Belopolsky, 2020;Arkesteijn, Smeets, Donk, & Belopolsky, 2018;Chou, Sommer, & Schiller, 1999;Coëffé & O'Regan, 1987;Deubel, Wolf, & Hauske, 1984;Findlay, 1981Findlay, , 1982Glimcher & Sparks, 1993;Heeman, Theeuwes, & van der Stigchel, 2014;Lee, Rohrer, & Sparks, 1998;McIlwain, 1986McIlwain, , 1991McSorley, Cruickshank, & Inman, 2009;McSorley & Findlay, 2003;Ottes, van Gisbergen, & Eggermont, 1984van Opstal & van Gisbergen, 1989;Walker & McSorley, 2008;Walker et al, 1997). The effect on landing position is known as the global effect or the center of gravity effect (Findlay, 1981;Findlay & Brown, 2006a, 2006bHe & Kowler, 1989).…”
Section: Introductionmentioning
confidence: 99%